O juiz cordial: atravessamentos e transversalidades do poder judiciário na democracia - Rodrigues, Vinícius dos Santos (Universidade do Vale do Rio dos Sinos, 2023)
The study aims to investigate the effects of judicial activism on Brazilian democracy and to identify some theoretical proposals that can balance the role of the courts. Democracy can be defined as a political ideal that seeks to promote equality among citizens and to reduce social inequalities. Thus, it was sought to analyze how the actions of judges and courts contributed to the increase or decrease of these factors. To understand the cultural formation of Brazilian society, it was used the work of Sérgio Buarque de Holanda, which describes a tradition of paternalism and cordiality. The judicial paternalism, exercised by these cordial judges, could be nourished by the structural mechanisms of the State bureaucracy, promoting the accumulation of symbolic power by the courts and the creation of a private language. In this perspective, the work used theoretical contributions from Pierre Bourdieu. Based on Gregório Baremblitt, an attempt was made to describe how the offer of judicial services found an echo in a needy and unequal society, suppressing collective knowledge, decision-making autonomy and the public debate of its citizens in favor of a technical knowledge of the courts. As a result, it was found that the activist role of the Judiciary, characterized as a true crossing, reduced equality in Brazil, as well as fostered the growth of social and economic inequalities. The creation of a private language by the courts diminished the possibilities of accountability and of a pluralist and agonistic democracy, in the terms proposed by Chantal Mouffe. Finally, this research presented some channels of transversality between the courts and society, such as the Hermeneutical Critics of Law (HCD), by Lenio Streck, and the opening of the constitutional jurisdiction, by Peter Häberle, which can develop democracy.
Keywords: Ativismo judicial; Democracia; Desigualdade; Judicial activism; Democracy; Inequality; ACCNPQ::Ciências Sociais Aplicadas::Direito